2018
DOI: 10.15632/jtam-pl.56.2.523
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical response of notched marble beams under bending versus acoustic emissions and electric activity

Abstract: An experimental protocol, including the combined application of both innovative and traditional sensing techniques, is described aiming to explore the mechanical response of marble and also to check the possibilities of detecting precursor phenomena designating upcoming catastrophic fracture. The protocol consisted of three-point bending tests with notched prismatic beams made of Dionysos marble, the material extensively used for restoration of the Acropolis of Athens monuments. The sensing system improvised i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Finally, it should be noticed that the general formulae including double and single caustics obviously refer also to opaque materials as particular cases of the transparent ones, provided their faces are properly polished. The latter could be of crucial importance, especially for specimens made of marble [50] and natural building stones [51], the mechanical response of which is usually studied using the Brazilian-disc test (due to insuperable difficulties encountered in the implementation of direct uniaxial tension tests, caused due to the unique nature of such materials [52][53][54][55][56]) employing either traditional or innovative experimental techniques [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noticed that the general formulae including double and single caustics obviously refer also to opaque materials as particular cases of the transparent ones, provided their faces are properly polished. The latter could be of crucial importance, especially for specimens made of marble [50] and natural building stones [51], the mechanical response of which is usually studied using the Brazilian-disc test (due to insuperable difficulties encountered in the implementation of direct uniaxial tension tests, caused due to the unique nature of such materials [52][53][54][55][56]) employing either traditional or innovative experimental techniques [57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
“…From b = β × 20/ ln (10), the maximum likelihood confidence limits of the b value with a narrow amplitude span in DTFAD can be obtained using Equation (17).…”
Section: Derivation Of Mle B Value and Confidence Limits Estimation S...mentioning
confidence: 99%
“…Additionally, since the selection of amplitude limits of the 'linear range' of the frequencyamplitude distribution and estimation method has a great influence on the calculation of the b value, considering the mean and standard deviation of the AE amplitude sample, Shiotani proposed the parameter of the Ib value (improved b value), which is also widely used to evaluate and monitor the fracture behavior of materials. Many studies have shown that the Ib value and the b value are different in size, but the change trend is the same [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The dimensions of the specimen were 20 × 20 × 100 mm 3 and the notch dimensions were 2.5 mm in width and 4 mm in length. The specimen was subjected to three-point bending under displacement-control mode at a rate of 0.01 mm/min [47]. So-called EXP-2 was conducted on a marble doubleedge notched specimen of dog-bone shape.…”
Section: Specimensmentioning
confidence: 99%